Niinwi - Kiinwa - Kiinwi: Building Non-Indigenous Allies in Education through Indigenous Pedagogy - Morcom, Lindsay; Freeman, Kate (Canadian Society for the Study of Education / Société canadienne pour l'étude de l'éducation, 2018)
In this article, we examine the Calls to Action of the Truth and Reconciliation Commission (TRC) of Canada (TRC, 2015a) in light of their implications for conscious ally-building in teacher education. Guided by the Anishinaabemowin language, the Medicine Wheel, and the Seven Grandfather Teachings, we ask what we can do to move from niinwi, “we but not you,” and kiinwa, “you all but not us,” to kiinwi, “you and us (together).” We arrive at the conclusion that reconciliatory education can be accomplished through respect and love, alongside an unyielding commitment to honouring Indigeneity, speaking truth, and building wisdom. Dans cet article, nous examinons les Appels à l’Action de la Commission de Vérité etRéconciliation (CVR) du Canada (2015a) au vu de leurs implications pour la construction consciente d’alliés dans la formation des enseignant(e)s. Guidées par la langue Anishinaabemowin, la Roue Médicinale, et les Enseignements des Sept Grand-Pères, nous demandons ce que nous pouvons faire pour passer de niinwi « nous mais pas vous », et kiinwa « vous mais pas nous », à kiinwi « vous et nous (ensemble) ». Nous arrivons à la conclusion qu’on peut accomplir l’éducation réconciliatrice par le respect et l’amour, ainsi qu’un engagement inébranlabable à honorer l’indigénéité, à dire la vérité, et à édifier la sagesse.